2016
DOI: 10.1016/j.ijpara.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Hydatigera taeniaeformis (Batsch, 1786) (Cestoda: Taeniidae) sensu lato with description of Hydatigera kamiyai n. sp.

Abstract: The common cat tapeworm Hydatigera taeniaeformis is a complex of three morphologically cryptic entities, which can be differentiated genetically. To clarify the biogeography and the host spectrum of the cryptic lineages, 150 specimens of H. taeniaeformis in various definitive and intermediate hosts from Eurasia, Africa and Australia were identified with DNA barcoding using partial mitochondrial cytochrome c oxidase subunit 1 gene sequences and compared with previously published data. Additional phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 53 publications
10
52
0
4
Order By: Relevance
“…In contrast, higher than expected functional host diversity for Hydatigera taeniaeformis suggests that, for this cosmopolitan tapeworm, the ecological niche of a prospective host species is not a strong determinant of host shifting. This is in line with the broad diversity of intermediate hosts recorded previously for this parasite (Lavikainen et al 2016). Notably, given the positive correlation in host association rates between non-carnivoran and carnivoran hosts observed for this tapeworm, a plausible explanation for this pattern is that the diversity of carnivoran hosts (mainly felids) with varying prey species in their diet facilitates host shifting to intermediate hosts across different ecological niches.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, higher than expected functional host diversity for Hydatigera taeniaeformis suggests that, for this cosmopolitan tapeworm, the ecological niche of a prospective host species is not a strong determinant of host shifting. This is in line with the broad diversity of intermediate hosts recorded previously for this parasite (Lavikainen et al 2016). Notably, given the positive correlation in host association rates between non-carnivoran and carnivoran hosts observed for this tapeworm, a plausible explanation for this pattern is that the diversity of carnivoran hosts (mainly felids) with varying prey species in their diet facilitates host shifting to intermediate hosts across different ecological niches.…”
Section: Discussionsupporting
confidence: 89%
“…Some records of host-parasite associations may be accidental records ('false positives') of parasites that have been recorded in a host species in which they cannot complete their life cycle. Moreover, references to parasite scientific names may involve some level of misclassification and crypto-diversity (de León and Nadler 2010); in the case of Hydatigera taeniaeformis, for example, it has been suggested that different subspecies circulate in different hosts (Lavikainen et al 2016). Modern molecular tools may shed further light on different lineages and subspecies of the examined parasite species.…”
Section: Sampling Bias and Cryptic Speciesmentioning
confidence: 99%
“…Hence re-description of these species has been necessary and driven primarily by their genetic signatures, i.e. H. taeniaeformis parasitizing voles has been re-described as Hydatigera kamiyai and T. mustelae as Versteria mustelae [6,7]. To the best of our knowledge, no such molecular studies, reporting the presence of newly raised species, have been carried out to date on cestode isolates from rodents in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Parasitation by Capillaria hepatica (Bancroft, 1893) was diagnosed macroscopically by the observation of whitish livers and then confi rmed microscopically (categorized as positive or negative) by the observation of the typically bi-polar eggs in lactophenol. Liver cysts were dissected to confi rm the presence of H. taeniaeformis larvae, identifi ed by their characteristic rostellar hooks (Lavikainen et al, 2016). Some of the recovered helminths species have not yet been identifi ed to species level since more material is still needed for full identifi cation and comparison, and because our aim was essentially to study zoonotic helminths.…”
Section: Methodsmentioning
confidence: 99%